Spinal or general anaesthesia for surgical repair of hip fracture and subsequent risk of mortality and morbidity: a database analysis using propensity score‐matching. (26th April 2020) - Morgan, L.; McKeever, T. M.; Nightingale, J.; Deakin, D. E.; Moppett, I. K.
Summary: Around 76, 000 people fracture their hip annually in the UK at a considerable personal, social and financial cost. Despite longstanding debate, the optimal mode of anaesthesia (general or spinal) remains unclear. Our aim was to assess whether there is a significant difference in mortality and morbidity between patients undergoing spinal anaesthesia compared with general anaesthesia during hip fracture surgery. A secondary analysis examined whether a difference exists in mortality for patients with pre‐existing cardiovascular disease or chronic obstructive pulmonary disease. This was a clinical database analysis of patients treated for hip fracture in Nottingham, UK between 2004 and 2015. Propensity score‐matching was used to generate matched pairs of patients, one of whom underwent each mode of anaesthesia. Data were analysed using conditional logistic regression, with 7164 patients successfully matched. There was no difference in 30‐ or 90‐day mortality in patients who had spinal rather than general anaesthesia (OR [95%CI] 0.97 [0.8–1.15]; p = 0.764 and 0.93 [0.82–1.05]; p = 0.247 respectively). Patients who had a spinal anaesthetic had a lower‐risk of blood transfusion (OR [95%CI] 0.84 [0.75–0.94]; p = 0.003) and urinary tract infection (OR [95%CI] 0.72 [0.61–0.84]; p < 0.001), but were more likely to develop a chest infection (OR [95%CI] 1.23 [1.07–1.42]; p = 0.004), deep vein thrombosis (OR [95%CI] 2.18 [1.07–4.45]; p = 0.032) or pulmonary embolism (OR [95%CI] 2.23 [1.16–4.29]; p = 0.016). The mode of anaesthesia for hip fracture surgery resulted in no significant difference in mortality, but there was a significant difference in several measures of postoperative morbidity. 요약: 영국에서 매년 약 76, 000명의 사람들에서 고관절 골절이 발 생하며 이는 상당한 개인적, 사회적, 경제적 대가를 수반한다. 오랜 논쟁에도 불구하고, 최적의 마취방법(전신 또는 척추)은 여전히 불분명하다. 저자들의 목표는 고관절 골절 수술 중 전 신마취와 비교하여 척추마취가 시행된 환자와의 사망률과 이 환율에 유의한 차이가 있는지를 평가하는 것이다. 2차 분석에 서는 기존 심혈관질환 또는 만성폐쇄성폐질환이 있는 환자에 서 사망률 차이가 존재하는지 조사하였다. 본 연구는 2004년 과 2015년 사이에 영국 노팅엄에서 고관절 골절로 치료받은 환자에 대한 임상 데이터베이스를 분석하였다. 선택바이어스 와 혼란변수 보정을 위하여 성향점수매칭을 이용하여 전신마 취와 척추마취를 시행받은 환자를 1대1로 매칭하였다. 조건부 로지스틱 회귀분석을 사용하여 데이터를 분석하였으며 7164 명의 환자가 성공적으로 짝을 이루었다. 전신마취가 아닌 척 추마취를 한 환자에서 30일 또는 90일 사망률은 차이가 없었 다(각각 오즈비[95% 신뢰구간] 0.97 [0.8–1.15]; p = 0.764 및 0.93 [0.82–1.05]; p = 0.247). 척추마취를 한 환자의 경우 수혈 (오즈비[95% 신뢰구간] 0.84 [0.75–0.94]; p = 0.003) 및 요로 감염(오즈비[95% 신뢰구간] 0.72 [0.61–0.84]; p ＜ 0.001)의 위 험은 낮았으나 흉부감염(오즈비[95% 신뢰구간] 1.23 [1.07–1.42]; p = 0.004), 심부정맥 혈전증(오즈비[95% 신뢰구간] 2.18 [1.07–4.45]; p = 0.032) 혹은 폐색전증(오즈비[95% 신뢰구간] 2.23 [1.16–4.29]; p = 0.016)이 발생할 가능성은 더 높았다. 고 관절 골절 수술을 위한 마취방법에 따른 사망률에는 큰 차이 가 없었지만, 수술 후 발생하는 다양한 이환율에는 유의한 차 이가 있었다.